Effects of cooperative learning on knowledge and ability of nursing students in health assessment using functional health pattern - Suwittawat, Chintana (Asia-Pacific Journal of Science and Technology, 2017)
The objectives of this research were to examine the effect of cooperative learning on knowledge and ability of nursing students in health assessment using Functional Health Pattern, and to assess the students’ opinions towards this teaching technique. The Sample was 12 second year nursing students of Faculty of Nursing, Khon Kaen University who registered for the course of 261 215 Fundamental Nursing Practice in the first semester of the 2013 academic year, selected by purposively sampling method. The research tools consisted of evaluation knowledge, practical skills, working group behavior observation from and the assessment questionnaire about the opinions to ward using coopera-tive learning. The One-Group Pretest-Posttest Design was employed in this study. Data were collected before and after the cooperative learning . The data were analyzed using SPSS for Window and presented in the form of maximum minimum mean and standard deviation. Comparison of learning knowledge before and after the cooperative learning by using paired samples t-test , the opinions of students were grouped as the similar information and report in the manner described . The results revealed that: 1.The knowledge mean score of nursing students in health assessment using Functional Health Pattern increased from 36.25+-1.96 to 39.67 ฑ1.78 after the cooperative learning 2. The ability of nursing students in health assessment using Functional Health Pattern at the highest level including Pattern 1 Health perception-health management (3.58+-0.49), Pattern 2 Nutritional-metabolic (3.67+-0.47 ), Pattern 8 Role-relationship (3.58+-0.49 ), and Pattern 10 Coping-stress tolerance (3.58+-0.49 ) 3. The knowledge mean score of nursing students in health assessment using Functional Health Pattern before and after was significantly different at the 0.05 level 4. Results of the survey of the students’ opinions towards this teaching technique revealed that the class had a funny environment, not stressful. The student interacted within the group. So the knowledge and the ability of nursing students in health assessment using Functional Health Pattern were increase. These findings demonstrate that. cooperative learning allows nursing students with the knowledge and ability in health assessment using Functional Health Pattern serving more. So the professor supervising nursing students how cooperative learning could be used to teach students.